(untitled) (Global Journal of Human-Social Science, 2015)
Rhetoric is the art of persuasion as opposed to a simple communication of information. The aim of rhetoric is not to spread truth and present it plainly and openly but to convince an audience to accept a speaker’s position - one which not necessarily congruent with that of the audience. The arguments alone cannot persuade, but when presented in a certain way, they become acceptable to the audience. Language is a device that enables us to understand the world. Speech is the expression of understanding (Sophia) which lets us explain situations, construct dialogue, and clarify and investigate the world. The word is the most powerful expression of human ability; without it human beings would have accomplished no more than animals intellectually. Communication is the essential activity that links the various parts of society together and allow them to function as n integrated whole. Rhetoricians understand the importance and power of words. They use strategies that rely on words, which they see as a tool to be use to effect, often in sophisticated ways. They seek to fashion a new reality, which the audience can accept as genuine. Rhetoricians generally do this by eliciting a sense of agreement with the listener and once that feeling of understanding has been established, the task of persuasion can begin.